The Effect Tiroksin Hormone (T4) Doses and Immersion Duration on Growth and Survival Rate of Tambaqui Larvae (Colossoma macropomum) - Dedy Syafri; Netti Aryani; Nuraini Nura (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
This research was conducted on October - November 2021, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Faculty of Riau University. The aim of this research was to determine the effect of Tiroksin Hormone (T4) and the optimal dose and different immersion duration on growth and survival rate of tambaqui fish larvae. The method used was a Completely Randomized Design Factorial with 2 factors. The first factor was the dose of tiroksin with 3 levels; 0 mg/L (D0), 0.05 mg/L (D0.05) and 0.1 mg/L (D0.1). The second factor was the immersion duration with three levels of 12 hours (P12), 24 hours (P24 and 36 hours (P36) respectively. The larvae were cultured preserved in aquarium for 40 days with 2 fish/L density. The results showed that the use of different doses and immersion duration of tiroksin effected on absolute weight, absolute length, specific growth and survival rate of tambaqui fish larvae. Treatment dose 0,1 mg /L and 24 hours (D0.1P24) showed the highest growth, namely absolute weight of 2.88 grams, absolute length 5.23 cm, specific growth rate of 18.44 % and survival rate of 85.66%. The water quality parameters during the research were optimal for tambaqui fish larvae with temperature 27.4 – 27.9 °C, pH 6.3-7.1, dissolved oxygen 6.3-7.1 mg/L, and ammonia 0.003-0.144 mg/L.